PENGARUH PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN DAN PARTISIPASI ANGGARAN TERHADAP PENGENDALIAN BIAYA (Studi pada BUMN di Kota Banda Aceh) - Jihan Rojana; Rulfah M. Daud; Jhon Andra Asmara (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
ABSTRACT: This study aims to determine whether the accountability effects on cost control, budget participation effects on cost control, and the accountability and budget participation have simultaneous effect on cost control. The population of this study included 73 managers and financial staff of state-owned companies in Banda Aceh. 20 companies were selected as the samples. This study used primary data for data collection by distributing questionnaires to managers and staff in the finance department of BUMN Banda Aceh. The methods used was multiple linear regression analysis with the help of the SPSS. Accountability has a significant effect on cost control, while budget participation has no effect on cost control. Accountability and budget participation provide simultaneous effect on cost control.